2006
DOI: 10.2174/156720206778792876
|View full text |Cite
|
Sign up to set email alerts
|

NRF2-Dependent Glutamate-L-Cysteine Ligase Catalytic Subunit Expression Mediates Insulin Protection Against Hyperglycemia-Induced Brain Endothelial Cell Apoptosis

Abstract: Increased oxidative stress and susceptibility of brain endothelium are contributing factors in the development of central nervous system complications in neuro-degenerative disorders in diabetes, Alzheimer's and Parkinson's disease. The molecular mechanisms underpinning the vulnerability of brain endothelial cells to chronic oxidative challenge have not been elucidated. Here, we investigated the oxidative susceptibility of human brain endothelial cells (IHEC) to chronic hyperglycemic stress and insulin signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
69
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 53 publications
14
69
1
Order By: Relevance
“…This author found that TOR was involved in the synthesis of Nrf2 protein in HepG2 cells. An in vitro study in human brain endothelial cells showed that elevated mTOR and S6K1 expression could up-regulate Nrf2 expression (Okouchi et al, 2006). The result of present study showed that 13.3 g kg −1 leucine supplementation significantly up-regulated TOR and S6K1 gene expression in the muscle.…”
Section: Protective Effect Of Leucine On Oxidative Damage In Musclementioning
confidence: 45%
“…This author found that TOR was involved in the synthesis of Nrf2 protein in HepG2 cells. An in vitro study in human brain endothelial cells showed that elevated mTOR and S6K1 expression could up-regulate Nrf2 expression (Okouchi et al, 2006). The result of present study showed that 13.3 g kg −1 leucine supplementation significantly up-regulated TOR and S6K1 gene expression in the muscle.…”
Section: Protective Effect Of Leucine On Oxidative Damage In Musclementioning
confidence: 45%
“…Nrf1, Nrf2, AP-1, NFκB and c-Myc seem to be involved in the regulation of the promoter activity of the GCLm gene (Wild et al, 1999;Yang et al, 2005;Benassi et al, 2006). Interestingly, it has been shown that insulin was unable to change the levels of GCLm mRNA (Okouchi et al, 2006), while GCLc levels were affected by this stimulus in the same report.…”
Section: +mentioning
confidence: 69%
“…Hence, being the most insulin-responsive brain area, the hypothalamus contributes to whole-body glucose homeostasis via IRS-PI 3-kinase signaling. The prime function of the other mechanism of neuroprotective action of insulin and IGF-1 realized via PI 3-kinase is to control the oxidative stress and susceptibility of the brain endothelium, the important contributing factors in the development of CNS disorders in DM (Okouchi et al, 2006). It was found that chronic hyperglycemia exacerbated apoptosis of human brain endothelial cells in accordance with exaggerated cytosolic and mitochondrial glutathione and protein-thiol redox imbalance.…”
Section: Insulin and Insulin-like Growth Factor-1mentioning
confidence: 99%
“…Insulin activates the PI 3-kinase/AKT kinase/mTOR kinase cascade, increases serine phosphorylation and nuclear translocation of nuclear NF-E2-related factor 2 (Nrf2), and enhances the expression of catalytic subunit of Nrf2-dependent glutamate-L-cysteine ligase, a heterodimeric enzyme participating in glutathione metabolism, and, hence, attenuates hyperglycemia-induced apoptosis via the restored cytosolic and mitochondrial redox balance. Inhibitors of IR tyrosine kinase, PI 3-kinase, AKT kinase and mTOR kinase abrogate insulin-induced Nrf2-mediated glutamate-L-cysteine ligase expression, redox balance, and the survival of human brain endothelial cells (Okouchi et al, 2006). Insulin-regulated PI 3-kinase-dependent pathways are involved in the prevention of endoplasmic reticulum stress that contributes to DM and neurodegenerative disorders (Hosoi et al, 2007).…”
Section: Insulin and Insulin-like Growth Factor-1mentioning
confidence: 99%